3D-printed woodpile structure for integral imaging and invisibility cloaking. (June 2020) - Zhu, Jian; Lao, Changshi; Chen, Tianning; Li, Jensen
Abstract: We present here the design, fabrication and experimental demonstration of a composite woodpile structure for integral imaging and invisibility cloaking. The structure composed of two layers of 3D-printed woodpile structure and a designed screen beneath it. The 3D display capability is first demonstrated by projecting a real 3D image from the screen. An invisibility carpet cloak is then demonstrated to hide an object on the ground in the visible regime by projecting a 3D virtual image of the ground from a pyramidal-shape screen. Comparing to transformation-optics-based or metasurface-based carpet cloaks, the current cloak can be both easily fabricated in large-scale simply using 3D printing and has an ultra-thin thickness with only 1.4 mm comparing to the height of the object of 4.7 mm. A polar viewing angle up to 20° with an arbitrary azimuthal viewing angle can be obtained with the present cloak. Our approach enables a cost-effective way towards practical 3D-printed optical components using the straight-forward fused deposition modeling method, leading to potential applications in 3D displays, integral microscopy, smart windows and augmented reality. Graphical abstract: Unlabelled Image Highlights: 3D display and invisibility based on woodpile-type lens array are achieved by projecting real and virtual 3D images. The cloaking effect can span a range of viewing angles while the cloak can be much thinner than the size of object. The extrusion-based 3D printing enables low-cost and large-scale fabrication for integral imaging.